PTH-035 Dilated common bile duct, stone size and multiple stones are predictors of endoscopic papillary large volume balloon dilatation in the management of complex common bile duct stones. (22nd June 2015) - Aujla, UI; Lee, HL; Robinson, EC; Noorullah, O; Dwyer, L; Stern, N; Hood, S; Sturgess, R
Abstract : Introduction: Endoscopic papillary large volume balloon dilatation (EPLVBD) has been used safely and effectively for stone removal in patients with complex common bile duct stones (CBDS). There remains a significant variation in practice particularly concerning the timing and preference to perform EPLVBD for removal of CBDS. Method: A single large volume tertiary referral centre study looking at factors predictive of EPLVBD for biliary stone removal and safety outcomes using a prospectively collected procedural database together with an electronic hospital clinical record. All ERCP records were interrogated over a period of five years from Oct 2009 to Sep 2014. Results: EPLVBD was performed in 202 patients (78 males and 124 females) with median age of 77 years (range 24–94). The main indication for performing ERCP was suspected biliary stone disease. 94(47%) patients had prior ERCP for stone disease and 108(54%) patients were undergoing their first ERCP. ERCP was performed predominantly under conscious sedation containing midazolam and fentanyl with median doses of 1.5mg (range 1.5–7) and 92.5 mcg (range 10–200) respectively. General anaesthesia was used in 34 patients. Median stone size was 10.09 mm (range 4–24) while median stone number was 2 (range 1–13). Distal, middle and proximal median common bile duct diameter were 10.68 mm (range 4–20), 13.37mm (range 9–28) and 12.66 mm (range 12–30) respectively. Median papillary balloon dilatation size was 15 mm (range 10–20). In 131 (65%) patients duct clearance was achieved with EPLVBD at first ERCP. In addition to EPLVBD, per-oral cholangioscopy (POC) and electrohydraulic lithotripsy (EHL) was performed in 14 and mechanical lithotripsy in 20 patients. 71(35%) patients did not achieve duct clearance at first ERCP. This was despite using mechanical lithotripsy in 30/71. Duct clearance was achieved at subsequent ERCP with POC and EHL in 30; mechanical lithotripsy in 7; repeat sphincteroplasty in 4 and extraction balloon in 34 patients. 40 patients (20%) had ampullary and peri-ampullary diverticulum. 23/40 (57%) had endoscopic sphincterotomy (ES) followed by EPLVBD at first ERCP without any complications. There were 2 cases of bleeding and pancreatitis (1%) each without any other procedural, sedation or anaesthesia related complications. Conclusion: EPLVBD is a safe and effective technique used to extract bile duct stones. There is no difference in outcomes whether it is performed at the time of sphincterotomy or at a later procedure or whether there is a full or limited sphincterotomy. Dilated CBD, stone size and presence of multiple stones are strong predictors of EPLVBD for biliary stone extraction. Disclosure of interest: None Declared.